2023
DOI: 10.1038/s41372-023-01634-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-course empiric antibiotic therapy for possible early-onset sepsis in the NICU

Abstract: Objective. On 2/2019, the Neonatal Antimicrobial Stewardship Program at Nationwide Children's Hospital recommended reducing empirical antibiotic therapy for early-onset sepsis (EOS) from 48 to 24 hours with a TIME-OUT. We describe our experience with this guideline and assess its safety.Methods. Retrospective review of all newborns evaluated for possible EOS at <72 hours of age at 6 neonatal intensive care units from 12/2018-7/2019. Safety endpoints were re-initiation of antibiotics within 7 days after discont… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…They are followed by clinical examinations, and antibiotic treatment is started only if symptoms of sepsis develop. Antimicrobial stewardship programs aimed at safely reducing administration of unwarranted antibiotic treatment and encouraging safe discontinuation of antibiotics within 36 to 48 hours have also been reported …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They are followed by clinical examinations, and antibiotic treatment is started only if symptoms of sepsis develop. Antimicrobial stewardship programs aimed at safely reducing administration of unwarranted antibiotic treatment and encouraging safe discontinuation of antibiotics within 36 to 48 hours have also been reported …”
Section: Discussionmentioning
confidence: 99%
“…Antimicrobial stewardship programs aimed at safely reducing administration of unwarranted antibiotic treatment and encouraging safe discontinuation of antibiotics within 36 to 48 hours have also been reported. 41 , 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our approach is similar to the one reported recently by Sanchez et al for treating EOS. 32 We based our decision to discontinue antibiotics earlier on our initial retrospective blood culture analysis that all the organisms involved in EOS became culture-positive in less than 24 hours. The study by Marks et al found that all but one of their positive blood cultures in EOS became positive within 24 hours.…”
Section: Discussionmentioning
confidence: 99%
“…In the most recent issue of the Journal of Perinatology, Sanchez et al report their results of a retrospective review assessing duration of empiric antibiotic use in 414 newborns undergoing an early onset sepsis (EOS) evaluation [1]. 24-hour and 48-hour empiric antibiotic courses were compared for safety endpoints including mortality and re-initiation of antibiotics within 7 days of discontinuation.…”
Section: To the Editormentioning
confidence: 99%